(untitled) (Publicaciones en Ciencias y Tecnología, 2014)
In this work a careful review describing diferent types of failures in electricalmachines, their characteristic signals generated and diagnosis methodsis performed. Additionally a comparison of the advantages between theknown failure detection methods based on the information required for diagnosis, the occurrence and importance of failures detection, the effectiveness for anticipating a mal function or failure and the final diagnosis accuracy is also made. Particularly, this review will help to provide a straight forward update about the most recent work and research in this field. The work is mainly oriented to engineering students interested in starting the researchand study of electrical machines.